Poverty Reduction and Growth Trust Interest Rate Mechanism : Extension of Temporary Interest Rate Waiver. (Policy Papers; Policy Paper, 2012)
In recent months, a number of Directors have expressed support in the Executive Board for a further extension of the temporary exceptional interest waiver on concessional lending. An extension would send a signal of the Fund's continued support for Low-Income Countries at a time when the global economic crisis is still ongoing. In view of the related downside risks to the global economic recovery and a decline in the ability of Low-Income Countries to respond to a further weakening of global growth, this paper proposes a further extension of the exceptional interest waiver by two years, to end-2014. This paper also proposes to further extend to April 2013 the existing subsidization of the rate of charge on outstanding Emergency Natural Disaster Assistance and Emergency Post-Conflict Assistance purchases by PRGT-eligible members.